Evaluation of analgesic effect, joint function recovery and safety of meloxicam in knee osteoarthritis patients who receive total knee arthroplasty: A randomized, controlled, double-blind study. Issue 35 (3rd September 2021) - Hu, Feng; Wu, Guoya; Zhao, Quan; Wu, Jian
Abstract : Abstract: Meloxicam is commonly administrated to control postoperative pain in orthopedic surgery, while its efficacy in total knee arthroplasty (TKA) is not clear. Therefore, this study aimed to explore the postoperative analgesic effect and tolerance of meloxicam in knee osteoarthritis (OA) patients undergoing TKA. Totally, 128 knee OA patients scheduled for TKA were enrolled in this randomized, controlled, double-blind study, then randomized into meloxicam group (N = 65) and control group (N = 63) as 1:1 ratio. Patients took meloxicam or placebo from 4 hours (h) to 72 h after TKA. Patients were followed up at 6 h, 12 h, day (D)1, D2, D3, D7, month (M)1, and M3. Pain visual analog scale score at rest was decreased in meloxicam group at 12 h, D1 and D3 compared to control group; pain visual analog scale score at flexion was reduced in meloxicam group at 6 h, 12 h, D1, D2, and D3 compared to control group. Additional and total consumption of patient-controlled analgesia were both attenuated in meloxicam group compared to control group. Furthermore, patient satisfaction score was higher on D1, D2, D3 in meloxicam group compared to control group. However, no difference of hospital for special surgery knee score score at M1 or M3 was found between the 2 groups. Moreover, the occurrence of adverse events was similar between the 2 groups. Meloxicam displays good effect on controlling postoperative pain and improving patient satisfaction, while does not affect long-term knee function recovery or safety profile in knee OA patients undergoing TKA.